Serotonin contributes to the in vitro production of a biomimetic enamel‐like material from reprogrammed oral epithelial keratinocytes. (11th February 2021) - Bazina, Fayrouz; Brouxhon, Sabine M.; Graham, Uschi M.; Kyrkanides, Stephanos
Abstract: Objectives: To evaluate the role of serotonin in the development of a biomimetic enamel‐like material in vitro. Setting and Sample population: Immortalized murine oral keratinocytes raised from adult mouse mucosa were cultured in vitro. In addition, specimens incorporating molar tooth buds harvested from mice were included in our studies. Materials and Methods: We used cell‐based scaffold‐free tissue engineering to assemble three‐dimensional (3D) organoids into complex tissue constructs that closely emulate the complexity of adult enamel. We also analysed mouse molar specimens using immunohistochemistry for serotonin expression as well as its cognate receptor. Results: TGF‐β1–reprogrammed murine oral keratinocytes formed organoids that laid down an amelogenin‐rich protein matrix when grown as three‐dimensional (3D) cultures in the presence of serotonin. Following mineralization, the newly formed crystals were densified under pressure and vacuum to produce a biomimetic enamel‐like material that demonstrated parallel alignment of hydroxyapatite crystals with some interspaced residual organoid matter into enamel prism‐like structures conferring size, mechanical properties comparable to tooth enamel, including light translucency. Serotonin expression was localized by immunohistochemistry proximal to the enamel organ of developing molar buds. Moreover, serotonin HTRb2 receptor expression was localized on ameloblasts within the enamel organ proximal to the area where serotonin was immunolocalized. Conclusions: Our results demonstrate that serotonin is inductive in the development of a biomimetic enamel‐like material from reprogrammed oral epithelial keratinocytes in vitro. The facileness of harvesting adult somatic cells together with the versatility of our approach offers exciting opportunities to address regenerative challenges linked to lost enamel.